Optimasi Kombinasi Limbah Abu Sekam Padi Dan Sikacim Untuk Percepatan Waktu Pengerasan Beton Fc’20 - Agus Setiobudi; Herri Purwanto; Amiwarti Amiwarti; Reffanda Kurniawan (Jurnal Tekno Global, 2026)
ABSTRACT Concrete road casting requires accelerated hardening to minimize traffic disruptions and reduce the impact of congestion. This research examines the effectiveness of combining Rice Husk Ash (RHA) as a partial cement replacement and Sikacim as a partial water replacement to enhance the hardening process of Fc'20 grade concrete. RHA was used to replace 5% of the cement content, while Sikacim was utilized as a water replacement with concentration variations of 5%, 10%, and 15% of the total mixing water requirement. The experimental methodology involved compressive strength testing on 24 standard cylindrical specimens after a 7-day curing period. The results indicated that the optimal combination of 5% RHA and 10% Sikacim achieved a compressive strength of 20.57 MPa at 7 days (equivalent to 31.65 MPa at 28 days), representing a 44.39% increase over the target Fc'20 quality. This performance boost resulted from the synergistic effect between the pozzolanic reaction of the RHA, which forms additional C-S-H (Calcium Silicate Hydrate) gel, and the superplasticizer properties of Sikacim, which improves workability while densifying the concrete matrix. The 5% Sikacim combination showed lower compressive strength due to an insufficient additive dosage to compensate for cement reduction, while 15% Sikacim led to potential segregation and hydration interference. These findings prove that 5% RHA with 10% Sikacim not only accelerates hardening but also significantly improves concrete quality. Implementing these findings provides a valuable contribution to speeding up road construction projects while promoting the sustainable use of local materials, specifically supporting green construction practices through the utilization of agricultural waste Keywords : Rice Husk Ash, Fc'20 Concrete, Concrete Compressive Strength, Rapid Concrete Hardening, Sikacim   ABSTRAK Pengecoran jalan beton memerlukan percepatan pengerasan untuk meminimalkan gangguan lalu lintas dan mengurangi dampak kemacetan. Penelitian ini mengkaji efektivitas kombinasi abu sekam padi (ASP) sebagai pengganti sebagian semen dan Sikacim sebagai pengganti sebagian air dalam meningkatkan proses pengerasan beton Fc'20. ASP digunakan untuk menggantikan 5% kandungan semen, sedangkan Sikacim digunakan sebagai pengganti air dengan variasi konsentrasi 5%, 10%, dan 15% dari total kebutuhan air campuran. Metodologi eksperimen melibatkan pengujian kuat tekan pada 24 spesimen silinder standar setelah periode perawatan 7 hari. Dari hasil penelitian didapatkan bahwa kombinasi optimal 5% ASP dan 10% Sikacim mencapai kuat tekan 20,57 MPa pada 7 hari, setara dengan 31,65 MPa pada 28 hari, terjadi peningkatan kuat tekan sebesar 44,39% dari mutu rencana Fc'20. Peningkatan kinerja ini dihasilkan dari efek sinergis antara reaksi pozzolanik ASP yang membentuk gel C-S-H tambahan, dan sifat superplasticizer Sikacim yang meningkatkan workability sekaligus memadatkan matriks beton. Kombinasi dengan 5% Sikacim menunjukkan kuat tekan yang lebih rendah karena dosis aditif yang tidak cukup untuk mengkompensasi pengurangan semen, sementara 15% Sikacim menyebabkan potensi segregasi dan gangguan hidrasi. Hasil ini membuktikan bahwa 5% ASP dengan 10% Sikacim tidak hanya mempercepat pengerasan beton tetapi juga secara signifikan meningkatkan kualitas beton. Implementasi temuan ini memberikan kontribusi berharga untuk mempercepat proyek konstruksi jalan sekaligus mendukung pemanfaatan bahan lokal yang berkelanjutan dalam industri konstruksi, khususnya mendukung praktik konstruksi hijau melalui pemanfaatan limbah pertanian. Kata Kunci : Abu Sekam Padi, Beton Fc'20, Kuat Tekan Beton, Pengerasan Beton Cepat, Sikacim